Evaluación de la prevalencia de caries y enfermedad periodontal en los pacientes con tratamiento de ortodoncia fija en la Facultad de Odontología, primer semestre de 1995 (1996)
ABSTRACT: Until the present moment there have not been studies to evaluate the dental and periodontal conditions of the patients in orthodontic treatment of the Faculty of Dentistry from the lIniversity of Antioquia. The objetive of this study was to determinat the oral hygiene (bacterian plaque index), dental health (COP index and incipient decay presence), and the periodontal conditions, (existence of gingival retraccions and gingival index). Furthermore the habits of oral hygiene, feeding habits, the time with the aparatology and its relation with each of the index were estabilized. The gingival index, plaque index and COP were also related with every variable: age, sex, educational level, level of instruction in oral hygiene. A total of 71 patients (28 men, 43 women) in ages between 10 and 24 years that had only orthodontic fix aparatology were evaluated, It was found that the plaque index were always bigger in the group of 10 to 14 year, and that the gingival index, and COP were lightly bigger in men than in women and that the gingival and plaque indexes. number of times that oral hygiene instruction was given, has positive influence in the COP, It was found also that the dental floss is used by a very low percentage of the patients and that the time with the orthodontic aparatology, can become a risk for the development of the tooth decay, because the actual COPs, was stadistically higher than the initial COPs.